La Fisica ad Arcetri Dalla nascita della Regia Università alle leggi razziali - Mazzoni, Massimo; Casalbuoni, Roberto; Dominici, Daniele; Pelosi, Giuseppe (I libri de «Il Colle di Galileo», 2016)
The exhibition: "La Fisica ad Arcetri. Dalla nascita della Regia Università alle leggi raziali" was organized by the Department of Physics and Astronomy of the University of Florence and by the Florence Section of the Italian National Institute of Nuclear Physics, in collaboration with the Historical Archive of the Municipality of Florence, the Physical Science and Natural Mathematics Library of the University of Florence, the Science and Technology Foundation, and the "Galileo" Museum of Florence. It was held from May to September 2016 in the Exhibition Hall of the Municipal Historical Archive in via dell'Oriuolo, Florence. The time covered by the exhibition ranges from the birth of the Royal University of Florence (1924) to the enactment of racial laws in Italy by Benito Mussolini's government (1938). The exhibited material comes from the Municipality's Historical Archive, the Garbasso Archive, the Della Corte Fund, the Department of Physics and Astronomy, the Science and Technology Foundation and from private collections. The catalogue is published as the third volume of the series of publications associated with the magazine «Il Colle di Galileo».